2009
DOI: 10.1111/j.1365-2036.2009.04091.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: music reduces anxiety levels in patients attending for endoscopy

Abstract: SUMMARY BackgroundPatients attending for endoscopy are generally anxious and worried.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 24 publications
(38 reference statements)
7
54
0
2
Order By: Relevance
“…This is congruent with results from a study by Ersöz et al (2010) who reported women to have a significantly higher state of anxiety than men prior to colonoscopy (Ersöz et al, 2010). This is also in line with earlier findings showing both men and women to be more anxious prior to a colonoscopy than they normally were (El-Hassan et al, 2009). In a randomized, controlled trial, patients who listened to self-selected music 15 minutes prior to colonoscopy reduced their anxiety level significantly more that patients who did not listen to music prior to the colonoscopy (Haynes et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…This is congruent with results from a study by Ersöz et al (2010) who reported women to have a significantly higher state of anxiety than men prior to colonoscopy (Ersöz et al, 2010). This is also in line with earlier findings showing both men and women to be more anxious prior to a colonoscopy than they normally were (El-Hassan et al, 2009). In a randomized, controlled trial, patients who listened to self-selected music 15 minutes prior to colonoscopy reduced their anxiety level significantly more that patients who did not listen to music prior to the colonoscopy (Haynes et al 2003).…”
Section: Discussionsupporting
confidence: 86%
“…Given this, the change of the mean pulse rate and mean blood pressure in the control group is likely to be higher. This supports a possible anxiolytic effect of music [12,13].…”
Section: Randomised Controlled Trial Of Music In Interventional Radiosupporting
confidence: 67%
“…Anxiety levels in patients attending for endoscopy were significantly reduced by listening to music (El-Hassan et al, 2009).…”
Section: During Interventional Proceduresmentioning
confidence: 92%